PELATIHAN PEMAHAMAN MENGENAI INFORMASI PEMASARAN PADA BISNIS KONVEKSI - Rasyid, Ardiansyah; Glacio, Rich; Meiwinka, Meiwinka; Fernando, Luis (PORTAL RISET DAN INOVASI PENGABDIAN MASYARAKAT, 2024)
A marketing information system is one that collects, manages, analyzes, and disseminates information related to marketing activities. This system includes various types of information, such as market data, consumer behavior, product or service performance, marketing campaign effectiveness, and competitor information. The aim of this outreach activity is to assist partners in enhancing their knowledge of marketing information to boost their competitive advantage. The partner organization operates in the garment industry and is located in Jakarta. The activity is conducted through training sessions focused on marketing information. This strategy also aids partners in improving customer understanding, market analysis, decision-making, and operational optimization. The training is conducted online via Zoom. The expected outcome of this activity is to resolve issues faced by the partner business and help them improve their business sustainability in marketing their products. The results of the activity will be published in journals and intellectual property rights (HKI).